“Dialectical thought” in “The Five Elements Theory” in ancient China - Dung, Vo Van (Argumentos - Revista de Filosofia, 2023)
The Five Elements Theory is one of the earliest theories in the history of Chinese philosophy. The birth of the doctrine marked a turning point in the process of perception of the world with the five basic elements of metal, wood and water, fire and earth. These five factors are perceived in the form of experience, the level of awareness is still rudimentary, and the most general characteristics of matter have not yet been generalized. However, with the two laws of the Five Elements of mutual birth, the five opposite elements complement each other when explaining the formation, development and transformation of the material world. These are two laws that are applied to explain the laws from nature, to society and the human body. The Five Elements Theory shows that things and phenomena in the universe and society do not stand still, but are always moving, changing and rotating constantly. In this article, we will focus on clarifying the dialectical thought of the theory of the Five Elements in nature, society and in the human body. The article will open up a new approach to the theory of the Five Elements and the next research direction is the application of the theory in oriental medicine.